Result of grafity and magnetic surveys on Mounts Merapi and Merbabu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT Gravity and magnetic surveys on mounts Merapi and Merbabu have been performed by S1 students of study Program of Geophysics, Physics departement, Faculty of Mathematics, Gadjah Mada University. Positive anomaly in gravitational and magnetic field have been found. Interpretation of the result yileds models of an excess mass and magnetic material under the Merapi and Merbabu Key words: gravity, magnetics, volcano